Polish word sketches - Radziszewski, Adam; Kilgarriff, Adam; Lew, Robert (Fundacja Uniwersytetu im. A. Mickiewicza, 2011)
Word sketches are one-page automatic, corpus-based summaries of a word's grammatical and collocational behaviour. They were first used in the production of the Macmillan English Dictionary (Rundell 2002). At that point, word sketches only existed for English. Today, the Sketch Engine is available, a corpus tool which takes as input a corpus of any language and corresponding grammar patterns and which generates word sketches for the words of that language. It also automatically generates a thesaurus and 'sketch differences', which specify similarities and differences between near-synonyms. A web corpus of Polish was morpho-syntactically tagged and loaded into the Sketch Engine. We describe the Polish Sketch Grammar and show how the resulting word sketches can be used in lexicography and for other linguistic purposes. The results show that word sketches could significantly facilitate lexicographic work for Polish, as they have for other languages.
Keywords: Polish; Lexical profiling; Sketch Engine; Word sketch; Concordancer; Web corpus; Collocation; Thesaurus; Morpho-syntactic description